GLABRA2 Regulates Actin Bundling Protein VILLIN1 in Root Hair Growth in Response to Osmotic Stress. Issue 1 (7th July 2020) - Wang, Xianling; Bi, Shuangtian; Wang, Lu; Li, Hongpeng; Gao, Bi-ao; Huang, Shanjin; Qu, Xiaolu; Cheng, Jianing; Wang, Shucai; Liu, Caiyuan; Jiang, Yikuo; Zhang, Bing; et al.
Abstract : VLN1, required for bundling actin filaments in root hair growth and transcriptionally regulated by GL2, negatively regulates osmotic stress-induced root hair growth. Abstract: Actin binding proteins and transcription factors are essential in regulating plant root hair growth in response to various environmental stresses; however, the interaction between these two factors in regulating root hair growth remains poorly understood. Apical and subapical thick actin bundles are necessary for terminating rapid elongation of root hair cells. Here, we show that Arabidopsis ( Arabidopsis thaliana ) actin-bundling protein Villin1 (VLN1) decorates filaments in shank, subapical, and apical hairs. vln1 mutants displayed significantly longer hairs with longer hair growing time and defects in the thick actin bundles and bundling activities in the subapical and apical regions, whereas seedlings overexpressing VLN1 showed different results. Genetic analysis showed that the transcription factor GLABRA2 (Gl2) played a regulatory role similar to that of VLN1 in hair growth and actin dynamics. Moreover, further analyses demonstrated that VLN1 overexpression suppresses the gl2 mutant phenotypes regarding hair growth and actin dynamics; GL2 directly recognizes the promoter of VLN1 and positively regulates VLN1 expression in root hairs; and the GL2-mediated VLN1 pathway is involved in the root hair growth response to osmotic stress. Our results demonstrate that the GL2-mediated VLN1 pathway plays an important role in the root hair growth response to osmotic stress, and they describe a transcriptional mechanism that regulates actin dynamics and thereby modulates cell tip growth in response to environmental signals.